Exosomes-based particles as inhalable COVID-19 vaccines - Fan Lu; Wang Li; Wang Xiaoju; Zhang Hongbo (Publishing services by Elsevier on behalf of KeAi Communications, 2025)
Coronavirus disease 2019 (COVID-19), a severely spreading pandemic, has dramatically brought physiological and economical burdens to people. Although the injectable vaccines have some achievements for coronavirus defense, they still generate accompanied pain, untoward reaction and cannot take part in mucosal immunity. Inhalable vaccines, as a safe, facile and efficient strategy, have been presented to protect body from virus by inducing robust mucosal immunity. Here, we give a perspective of an inhalable COVID-19 vaccine composed of lung-derived exosomes (a type of virus-like particle) conjugated with viral receptor-binding domain. The lung-derived exosomes act as carriers, such inhalable particles successfully reach at lung and reveal wider distribution and longer retention on respiratory mucosa. In addition, such vaccines induce the high production of specific antibodies and T cells in lung, significantly protecting host against coronavirus invasion. It is conceived that inhalable virus-like particles with long-term stability wound open a new avenue for vaccines delivery and further achieve vaccine popularization to against with COVID-19 pandemic.